TRAUMA DALAM NOVEL YU ZHEN - Livia Vasantadjaja (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2017)
《余震》Yu Zhen or After Shock (2006) is a novel written by Zhang Ling, a Chinese woman writer who lives in Canada now. After Shock  is a story about the great earthquake happened at Tangshan city, Hebei province, P.R.C in 1976. One interesting point to discuss from this novel is about Wan Xiaodeng’s emotional states and conditions as a main character, as well as an earthquake victim in this novel. Wan Xiaodeng not only suffers from physical trauma, but also suffers from acute psychological trauma.This psychological trauma existed from her childhood to adulthood. By psychological point of view, this writing is going to discuss Wan Xiaodeng’s symptoms of post traumatic stress disorder, and impacts or responses to the surroundings. Keywords:《余震》Yu Zhen, After Shock, Zhang Ling, trauma